2006
DOI: 10.1158/0008-5472.can-06-1854
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Reoxygenation after Antiangiogenic Therapy Using SU5416 and Its Importance for Guiding Combined Antitumor Therapy

Abstract: Emerging preclinical studies support the concept of a transient ''normalization'' of tumor vasculature during the early stage of antiangiogenic treatment, with possible beneficial effects on associated radiotherapy or chemotherapy. One key issue in this area of research is to determine whether this feature is common to all antiangiogenic drugs and whether the phenomenon occurs in all types of tumors. In the present study, we characterized the evolution of the tumor oxygenation (in transplantable liver tumor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 29 publications
1
43
0
1
Order By: Relevance
“…Recently, transient improvement in tumor pO 2 by antiangiogenesis drugs has been getting increasing attention to improve radiotherapy efficacy (43). A combination of pO 2 maps obtained by EPRI and perfusion-weighted images by MRI will contribute to a better understanding of tumor oxygen status and its relationship with other blood flow and metabolic profiles, making it possible for a more detailed planning of combination therapy of anticancer drugs and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transient improvement in tumor pO 2 by antiangiogenesis drugs has been getting increasing attention to improve radiotherapy efficacy (43). A combination of pO 2 maps obtained by EPRI and perfusion-weighted images by MRI will contribute to a better understanding of tumor oxygen status and its relationship with other blood flow and metabolic profiles, making it possible for a more detailed planning of combination therapy of anticancer drugs and radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic paramagnetic resonance (EPR) oximetry, using charcoal (CX0670-1; EM Science) as the oxygensensitive probe, was used to evaluate tumor and muscle oxygenation as previously described (33). EPR spectra were recorded using an EPR spectrometer (Magnettech) with a low frequence microwave bridge operating at 1.2 GHz and extended loop resonator.…”
Section: Methodsmentioning
confidence: 99%
“…The suspension was drawn into glass capillary tubes; cytotoxicity was concomitantly evaluated with a 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay (34). All spectra were recorded on a Bruker EMX EPR spectrometer operating at 9 GHz, as previously described (33). The probe was calibrated at various O 2 concentrations between 100% nitrogen and air so that the line width measurements were related to O 2 concentration at any value.…”
Section: Methodsmentioning
confidence: 99%
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…Lee et al 2000;Winkler et al 2004;Dings et al 2007;Fischer et al 2007;Eichhorn et al 2008;Batra et al 2009;Skuli et al 2009;McGee et al 2010. j Teicher et al 1995bJain et al 1998;Bernsen et al 1999;Cohen-Jonathan et al 2001;Delmas et al 2003;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006b;Segers et al 2006;Cerniglia et al 2009;Qayum et al 2009;Cham et al 2010. k Ader et al 2003;Hamzah et al 2008;Kashiwagi et al 2008;Stockmann et al 2008;Maione et al 2009;Mazzone et al 2009;Skuli et al 2009;Tsukada et al 2009;Rolny et al 2011. l Yuan et al 1996Lee et al 2000;Wildiers et al 2003;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Kurozumi et al 2007;Taguchi et al 2008;Zhou et al 2008;Kamoun et al 2009;Ohta et al 2009;Gallo 2009. m Jain et al 1998;Izumi et al 2002;…”
Section: Vegfunclassified